2021
DOI: 10.1158/1078-0432.ccr-20-4726
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin Plus Pembrolizumab in Patients with Metastatic Triple-Negative Breast Cancer (ENHANCE 1): A Phase Ib/II Study

Abstract: V Kaklamani has participated in a speaker bureau for, as well as received honoraria and research funding from, Eisai. DD'A is an employee of Eisai Inc.GA and an immediate family member are employees of Merck Sharp & Dohme Corp., a

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 25 publications
7
71
2
1
Order By: Relevance
“…Of the 44 patients in the trial treated with eribulin and pembrolizumab, 21 (48%) had irAEs, including 2 patients who experienced both immune-related colitis and grade 5 sepsis 6 . Compared to other trials of ICIs with chemotherapy in metastatic breast cancer, this irAE frequency was similar to ENHANCE-1 (pembrolizumab with eribulin; 43%) 38 and IMpassion130 (atezolizumab with nab-paclitaxel; 57%) 8 but higher than KELLY (pembrolizumab with eribulin; 25%) 39 and KEYNOTE-355 (pembrolizumab with nab-paclitaxel, paclitaxel, or gemcitabine plus carboplatin; 26%) 40 , indicating wide heterogeneity that may be attributable to the lack of a standardized definition for irAEs 41 , 42 . In the present trial, patients with vs. without irAEs had no difference in PFS or OS (HR for progression 0.8, 95% CI 0.5–1.4, p = 0.5; HR for death 0.8, 95% CI 0.4–1.4, p = 0.4; Supplementary Data File 1 : Supplementary Table 8 ), which differs from previous studies showing that irAEs correlate with improved ICI responses 43 , 44 , likely because our analysis addressed the possibility of guarantee-time bias 45 .…”
Section: Resultssupporting
confidence: 67%
“…Of the 44 patients in the trial treated with eribulin and pembrolizumab, 21 (48%) had irAEs, including 2 patients who experienced both immune-related colitis and grade 5 sepsis 6 . Compared to other trials of ICIs with chemotherapy in metastatic breast cancer, this irAE frequency was similar to ENHANCE-1 (pembrolizumab with eribulin; 43%) 38 and IMpassion130 (atezolizumab with nab-paclitaxel; 57%) 8 but higher than KELLY (pembrolizumab with eribulin; 25%) 39 and KEYNOTE-355 (pembrolizumab with nab-paclitaxel, paclitaxel, or gemcitabine plus carboplatin; 26%) 40 , indicating wide heterogeneity that may be attributable to the lack of a standardized definition for irAEs 41 , 42 . In the present trial, patients with vs. without irAEs had no difference in PFS or OS (HR for progression 0.8, 95% CI 0.5–1.4, p = 0.5; HR for death 0.8, 95% CI 0.4–1.4, p = 0.4; Supplementary Data File 1 : Supplementary Table 8 ), which differs from previous studies showing that irAEs correlate with improved ICI responses 43 , 44 , likely because our analysis addressed the possibility of guarantee-time bias 45 .…”
Section: Resultssupporting
confidence: 67%
“…culture (Komlodi-Pasztor et al, 2011). These findings are timely as they may contribute to a mechanistic understanding behind the efficacy of combinations of molecularly distinct classes of MTAs, including eribulin, with immune checkpoint inhibition in TNBC patients (Schmid et al, 2020;Tolaney et al, 2021). The cGAS-STING pathway has been shown to be indispensable for immune checkpoint inhibitors to exert their antitumor effects (Wang et al, 2017) and agents that activate the cGAS-STING pathway have been shown to enhance the efficacy of immune checkpoint therapy in metastatic breast cancer models primarily by priming the immune system to acquire an antitumor phenotype (Chandra et al, 2014;Cheng et al, 2018).…”
Section: Discussion 873/1500mentioning
confidence: 97%
“…Although some of the compound or class-specific immunomodulatory effects of MTAs, such as the ability of paclitaxel to directly activate TLR4-dependent signaling (Rajput et al, 2013;Wanderley et al, 2018), have been extensively explored, many of the underlying mechanisms of how MTAs elicit distinct immunological effects are unknown. A more complete interrogation of the effects of MTAs on immune signaling pathways is warranted given the recent clinical evaluations of MTAs, including taxanes and eribulin, in combination with immune checkpoint inhibitors to enhance the therapeutic response in metastatic triple-negative breast cancer (TNBC) (Mittendorf et al, 2020;Schmid et al, 2020;Tolaney et al, 2021).…”
Section: Introduction 353/750mentioning
confidence: 99%
“…The combination of eribulin with a checkpoint inhibitor was anticipated to exert favorable antitumor effects, due to a combination of cytotoxic effect from the chemotherapeutic agent and restoration of tumor-specific T cell response. In ENHANCE-1, clinical activity was most pronounced in patients with PD-L1-positive tumors and treated first line (ORR CPS ≥ 1 34.5% vs 16.1%; CPS ≥ 10 30.8% vs 23.4%) [31].…”
Section: Immune Checkpoint Inhibitors Combined With Chemotherapymentioning
confidence: 99%